Tax Avoidance in Influencing The Firm Value - Ardelia, Dea Devina; Irma Suryani; Syahrudin, Syahrudin (Journal of Accounting Inaba, 2023)
The purpose of this study is to determine how tax avoidance affects the value of coal mining companies listed on the Indonesian stock exchange from 2018–2022. Associative descriptive research is the quantitative methodology employed in this study. Purposive sampling was the method of sampling that was employed in this study. The sample in the research obtained through the sample selection criteria was 10 companies with a total of 50 samples. The data source obtained from this research is secondary using financial reports from 10 companies according to sampling criteria from 2018 to 2022. The study's findings demonstrate that tax evasion significantly and negatively affects a company's worth. The tax avoidance variable has a value of 0.238 > 0.05 according to the results of hypothesis testing based on probability values, indicating that this independent variable has no discernible impact on the company value of coal mining companies listed on the Indonesian stock exchange in 2018–2022